2013
DOI: 10.1038/ncb2773
|View full text |Cite
|
Sign up to set email alerts
|

MUS81 promotes common fragile site expression

Abstract: Fragile sites are chromosomal loci with a propensity to form gaps or breaks during early mitosis, and their instability is implicated as being causative in certain neurological disorders and cancers. Recent work has demonstrated that the so-called common fragile sites (CFSs) often impair the faithful disjunction of sister chromatids in mitosis. However, the mechanisms by which CFSs express their fragility, and the cellular factors required to suppress CFS instability, remain largely undefined. Here, we report … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
268
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 242 publications
(292 citation statements)
references
References 31 publications
17
268
0
1
Order By: Relevance
“…MUS81 and ERCC1 are important for common fragile site breakage (or ''expression'') during G2/M phase, a process that aids faithful chromosome disjunction by severing intertwined DNA strands at sites of ongoing/incomplete replication (Naim et al 2013;Ying et al 2013). Consistent with this, MUS81-and ERCC1-depleted cells exhibit high frequencies of segregation defects and 53BP1-positive G1 nuclear bodies (NBs), in particular when subjected to exogenous replication stress.…”
mentioning
confidence: 57%
“…MUS81 and ERCC1 are important for common fragile site breakage (or ''expression'') during G2/M phase, a process that aids faithful chromosome disjunction by severing intertwined DNA strands at sites of ongoing/incomplete replication (Naim et al 2013;Ying et al 2013). Consistent with this, MUS81-and ERCC1-depleted cells exhibit high frequencies of segregation defects and 53BP1-positive G1 nuclear bodies (NBs), in particular when subjected to exogenous replication stress.…”
mentioning
confidence: 57%
“…However, simultaneous depletion of WRN and RAD51 does not suppress these DSBs, suggesting that MUS81 operates upstream of RAD51 in the processing of toxic replication intermediates (Franchitto et al, 2008;Murfuni et al, 2012;Murfuni et al, 2013). Furthermore, MUS81 also plays a role in the cleavage of RFs remaining at later (G2/M) stages of the cell cycle at common fragile sites, and its absence leads to an increase in anaphase bridges due to improper disjunction of sister chromatids (Naim et al, 2013;Ying et al, 2013;Pepe and West, 2014). Much less is known about the potential role of GEN1/Yen1 in facilitating replication of difficult to replicate regions, although both yeast and mammalian cells lacking MUS81 and GEN1/Yen1 show increased genome instability compared with the corresponding single mutants (Ho et al, 2010;Agmon et al, 2011;Wyatt et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it has recently been shown that the MUS81-EME1 nuclease is responsible for chromatid breakages observed at CFSs (Fig. 5C) (Naim et al 2013;Ying et al 2013). Taken all together, mitotic cells could manage to separate replication intermediates through two alternative mechanisms: one is MUS81-mediated DNA cleavage, resulting in CFS breakage, and the other is BLM-mediated dissolution, involving UFB formation.…”
Section: Mitotic Chromosome Dynamicsmentioning
confidence: 99%